Diagnostic performance of the Brief Cognitive Screening Battery-Indonesian version in detecting cognitive impairment - Fitri, Fasihah Irfani; Nazriani, Dina; Dachi, Octaviasari Agatha; Nitrini, Ricardo; Caramelli, Paulo (Arquivos de Neuro-Psiquiatria, 2025)
Neuropsychological and functional assessments are crucial for identifying the transition from healthy aging to dementia. While brief cognitive batteries have become popular for their practicality, most have been developed in high-income countries, neglecting the diverse educational backgrounds found in developing nations.This study focuses on the Brief Cognitive Screening Battery (BCSB) adapted for Indonesia (BCSB-INA), aiming to investigate its diagnostic accuracy in detecting cognitive impairment among older adults.This cross-sectional study was conducted at the Memory Clinic of Universitas Sumatera Utara Hospital from January to August 2024, including participants aged 50 and above. Subjects underwent cognitive assessments using MoCA-INA and BCSB-INA. Data analysis involved ROC curves to evaluate the tests' accuracy.A total of 140 subjects were included, with significant differences in cognitive test scores between those with cognitive impairment and normal individuals. The BCSB-INA demonstrated good diagnostic performance, with an AUC of 0.875 when including the Clock Drawing Test (CDT) and 0.810 without it. The development of a multivariate model further enhances its diagnostic capabilities, allowing for more tailored intervention strategies.The BCSB-INA represents an important improvement in cognitive assessment for older adults in Indonesia, showing good sensitivity and specificity. Continued research and updates to cognitive assessment tools are crucial to meet the increasing demand for effective dementia screening in diverse populations.
Keywords: Brief Cognitive Screening Battery; Cognition; Dementia; Indonesia